A management of technology framework for MSME success and sustainability (Philippine Management Review, 2010)
In this article, management of technology (MOT) is defined as the application of science, engineering and managerial knowledge for the effective identification, selection, acquisition, development, exploitation, and protection of technologies appropriate for the production and delivery of goods and services necessary for the organization to gain competitive advantage and attain desired levels of growth and performance. This definition serves as the general framework that is used to guide the development of the various sections of the paper. A profile of MSMEs is presented which provides information on the structural features of Philippine MSMEs and key issues concerning this sector, such as competitiveness, productivity, funding and access to markets. Another component of this paper is a section on government programs for MSME promotion and development, which include the SMED Plan 2004-2010 and the Department of Science and Technology's (DOST) Small Enterprise Technology Upgrading Program (SETUP). Another major part of this paper consists of three case studies that highlight unique and high-performing small enterprises : Innovatronix Incorporated, Digital Infostructure and Consulting Corporation, and MoonDish Foods Corporation. The case studies focus on the identification of strengths, weaknesses, opportunities, threats, and most important of all, the factors that have been identified as critical to their success. The final sections of the article consist of the recommendations and conclusion. The recommendations have been categorized into two : (1) recommendations to enterprises; and (2) recommendations to government.